(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Building sector is known as one of the biggest polluters, causing environmental pollution and carbon dioxide emissions, most of which are generated during the production process of building materials. Therefore, researchers and manufacturers have become increasingly interested in environmentally friendly materials with low energy consumption. Magnesium based cements are being studied as an alternative to a widespread material as Portland cement, thus reducing the temperature required for calcination. During this research, magnesium binder-based composites using two types of magnesium (local dolomite waste material and caustic magnesia) were produced. Within the framework of this study, several regimes of thermal treatment were used to produce low carbon dioxide and environmentally friendly magnesium binder composites. Physical, mechanical and thermal properties of obtained specimens were tested.